The diagnostic significance of pupillary reflex pathways: insights from classical examination and advanced pupillometry - Lisowski, Łukasz; Lisowska, Jolanta; Charytonowicz, Anna; Mariak, Zofia; Obuchowska, Iwona; Konopińska, Joanna (Frontiers in Neuroscience, 2025)
Background/objectivesThe pupil, a dynamic ocular structure, serves as a critical indicator of neurological and ophthalmological function. This interdisciplinary review explores the anatomical, physiological, and pathological aspects of pupillary reflexes and disorders.ContentEmphasis is placed on the diagnostic relevance of light and accommodation reflexes, sympathetic and parasympathetic pathways, and the clinical implications of conditions such as Horner’s syndrome, Adie’s tonic pupil, and Argyll Robertson pupil. The utility of pharmacological testing and pupillometry in localizing lesions and identifying subclinical changes is extensively discussed. Advancements in pupillary assessment–particularly dynamic and chromatic pupillometry–offer novel insights into autonomic nervous system dysfunction, neurodegenerative diseases, and retinal pathologies including glaucoma and retinitis pigmentosa.Recent findingsBy integrating classical examination techniques with modern imaging and measurement modalities, the pupil emerges as a valuable biomarker in systemic, neurological, and psychiatric disorders. This review underscores the necessity of collaborative, multidisciplinary approaches for accurate diagnosis and effective management of pupillary abnormalities.ConclusionParticular attention is given to the diagnostic and prognostic applications of pupillometry, the pathophysiological mechanisms underlying pupillary abnormalities, and the utility of pharmacological tests in lesion localization. By consolidating foundational knowledge with recent clinical and technological developments, this review offers an updated framework for understanding pupillary function and dysfunction and highlights the importance of collaborative approaches across medical specialties for improved diagnostic accuracy and patient care.